Emergency Remote Education Satisfaction during COVID-19 at a Public University in Central Andes, Peru with Low Resources and Little Online Teaching Experience - Castro-Bedriñana, Jorge (2022)
Emergency measures to continue university activities during COVID-19 have affected student performance and satisfaction, especially in regions with scarce resources and little experience in virtual education. Online education is a new process for most universities in the interior of Peru, where digital transformation was null or incipient, affecting the learning effectiveness. The current research is based on a survey conducted in February 2021 in order to evaluate students’ perception about the quality of emergency remote learning measures introduced during the pandemic in 2020. The survey was distributed through the institutional emails of students and the responses were collected anonymously, following a systematic sampling. A total of 1029 respondents representing 38 professional careers of public referent university of the Central Andes of Peru participated in this survey. The survey focused on 28 criteria linked to the didactic, technological and psycho-affective dimensions. It aimed to collect scientific evidence to propose improvements in this pedagogical transition process. Associations between the variables studied were determined with χ2 tests and Spearman correlations, and to determine the regression coefficients and Odds Ratios of the variables associated with the highest degree of satisfaction with the emergency virtual classes, logistic regression was used. Thirty percent of students showed dissatisfaction, perceiving problems in the design of class materials, feedback, e-learning support, development of practical and laboratory activities, and teaching performance; 25% were satisfied and 45% had a neutral perception. About 30% felt frustrated with their virtual classes. The highest OR for a higher degree of satisfaction fell on the impact of courses for professional training, student care services, support for online learning, and feedback mechanisms. To improve the quality of virtual learning in the post-pandemic period, the study recommends to transform the face-to-face model to a virtual or blended model, taking advantage of the variety of information, and communication to improve the quality of higher education.